GENERATIVE APPROACHES TO BEHDINI-KURDISH STUDENTS' ACQUISITION OF ENGLISH PASSIVIZATION - Toma, Shivan (Humanities Journal of University of Zakho, 2024)
This research examines how Behdini-Kurdish students acquire passive voice in English, focusing on the interaction between their innate linguistic abilities and external language input. Using a mixed-methods approach, the study investigates the strategies used by Kurdish learners on acquiring passive voice constructions, which pose a notable challenge for many individuals learning English as a foreign language. By analyzing the cognitive processes and tactics used by these students, this research aims to contribute to a deeper understanding of the mechanisms involved in second language acquisition (SLA) from the perspective of generative grammar. Preliminary observations suggest that Kurdish students' acquisition of the passive voice in English is influenced by factors such as the linguistic structure of their native language, exposure to language input, and their inherent language acquisition ability. This study emphasizes the importance of tailored pedagogical strategies that align with the theories of generative grammar to enhance Kurdish students' competence in mastering passive voice structures in English. Practical results show that explicit instruction and increased exposure to passive constructions in English significantly improve learners' proficiency. In addition, error analysis reveals common problems with verb forms and agent placement, necessitating focused educational interventions. This study provides important insights into the challenges faced by Behdini-Kurdish students in acquiring passive voice structures in English. Several key conclusions are drawn from this study including challenges in learning passive voice in English among the majority of Behdini-Kurdish learners due to the effect of language transfer in most cases.